Experimental study on cyclic behaviour of riveted stiffened seat angle connections. - Haj Khan Mirza Sarraf, Majid. (University of Ottawa (Canada), 1994)
Riveted Stiffened Seat Angle Connections have been used as beam-to-column joints in many old steel buildings. These connections are generally categorized as flexible. A concern exists as to the lateral resistance of frames built with these connections, particularly under earthquake excitations which can cause these connections to undergo severe inelastic excursions. An experimental program was conducted to investigate the behaviour of two typical Riveted Stiffened Seat Angle Connections and the improvement in their behaviour when retrofitted using two suggested retrofitting techniques. Large inelastic cyclic tests were conducted on connections taken from an 83 years old building and their hysteretic moment-rotation curves were obtained. Preliminary models of their inelastic behaviour are developed. Practical recommendations for seismic rehabilitations are formulated.
Keywords: Engineering, Civil.